2016
DOI: 10.25095/mufad.396708
|View full text |Cite
|
Sign up to set email alerts
|

Ekonomik Kriz Ortamında KOBİ’lerin Mali Başarısızlıktan Korunma Stratejilerinin İncelenmesi:TR 22 Bölgesinde Bir Araştırma

Abstract: SMEs take significant roles for Turkish Economy to maintain its stability. However, these businesses are unavoidably affected by the economic crises of both national and international level. Stabilizing their position under the market conditions where the crises occur and the strategies that they implement in order to avoid from the financial failures have critical importance. Core to the mentioned strategies remains the decisions taken at accounting and finance bases. In this scope, a survey has been designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In such cases, operators should take advantage of crises and try different methods. In fact, crises should be regarded as a stepping stone that increases the success of the business(Erol, 2010).Although private sports operators experienced anxiety about the future, economic difficulties and psychological problems, they made their best efforts to support their members and to keep them doing sports during this process. In summary, it has been observed that when the sports halls are closed, the operators do not stop communicating with their members, they constantly support their members both by phone and through social media applications, they enable them to do their exercises at home, some operators provide psychologist, dietician and physiotherapist support to their members online, and some operators provide…”
mentioning
confidence: 99%
“…In such cases, operators should take advantage of crises and try different methods. In fact, crises should be regarded as a stepping stone that increases the success of the business(Erol, 2010).Although private sports operators experienced anxiety about the future, economic difficulties and psychological problems, they made their best efforts to support their members and to keep them doing sports during this process. In summary, it has been observed that when the sports halls are closed, the operators do not stop communicating with their members, they constantly support their members both by phone and through social media applications, they enable them to do their exercises at home, some operators provide psychologist, dietician and physiotherapist support to their members online, and some operators provide…”
mentioning
confidence: 99%